2018
DOI: 10.3310/eme05030
|View full text |Cite
|
Sign up to set email alerts
|

Functional strength training versus movement performance therapy for upper limb motor recovery early after stroke: a RCT

Abstract: Background Not all stroke survivors respond to the same form of physical therapy in the same way early after stroke. The response is variable and a detailed understanding of the interaction between specific physical therapies and neural structure and function is needed. Objectives To determine if upper limb recovery is enhanced more by functional strength training (FST) than by movement performance therapy (MPT), to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Randomized controlled trials are the gold standard for evaluating treatment effectiveness. Major stroke rehabilitation trials so far have shown only marginal effectiveness in improvement of motor function compared to the standard of care (2,5,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). In the US, a stroke occurs every 40 sec (37); most individuals survive but with long-term motor impairments that seriously limit independent living.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials are the gold standard for evaluating treatment effectiveness. Major stroke rehabilitation trials so far have shown only marginal effectiveness in improvement of motor function compared to the standard of care (2,5,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). In the US, a stroke occurs every 40 sec (37); most individuals survive but with long-term motor impairments that seriously limit independent living.…”
Section: Discussionmentioning
confidence: 99%
“…Two-thirds of the individuals with stroke do not recover the necessary upper extremity (UE) function for usual activities by 6 mo, when motor recovery typically plateaus ( 12 14 ). To date the majority of randomized stroke rehabilitation trials have demonstrated limited efficacy in motor recovery ( 15 26 ).…”
mentioning
confidence: 99%
“…FST consisted of progressive resistive exercise during functional tasks and MPT of "hands on" guidance for smooth and accurate movements. No significant intergroup differences were observed at the end of intervention (ARAT, WMFT, hand and pinch grip force) (Pomeroy et al 2018).…”
Section: Strength Trainingmentioning
confidence: 72%